Toward carbon free energy. - Sweet, W.
In this paper the authors describe how heavy reliance on coal in huge countries like China and India threatens the whole world's climate. They state how they believe that the utmost ingenuity will be needed to minimize adverse effects of that dependence
Keywords: China; India; Carbon free energy; Coal; Renewable energies; World climate